Seasonal variation in hospitalization outcomes in patients admitted for heart failure in the United States. Issue 11 (5th September 2017) - Akintoye, Emmanuel; Briasoulis, Alexandros; Egbe, Alexander; Adegbala, Oluwole; Alliu, Samson; Sheikh, Muhammad; Singh, Manmohan; Ahmed, Abdelrahman; Mallikethi‐Reddy, Sagar; Levine, Diane
Abstract : Background: There is lack of evidence of the impact of varying season on heart failure (HF) hospitalization outcomes in the U.S. Hypothesis: HF hospitalization outcomes exhibit significant seasonal variation in the U.S. Methods: Using data from the National Inpatient Sample (2011‐2013), seasonal variation was classified based on meteorological classification of Northern Hemisphere–Spring, Summer, Fall, & Winter–and analysis was conducted via multivariable‐adjusted mixed‐effect model. Results: An estimated 2.8 million adults were hospitalized for HF in the U.S. from 2011 to 2013. Of all hospitalizations, admissions were highest in Winter (27%), followed by Spring (26%), Fall (24%), and Summer (23%). The overall mortality rate was 3.1%. Compared with Spring, there was significantly lower mortality in Summer (odds ratio [OR]: 0.95, 95% CI: 0.91‐0.99) and Fall (OR: 0.94, 95% CI: 0.89‐0.98), but the highest mortality was in Winter (OR: 1.06, 95% CI: 1.02‐1.11). In addition, mean length of stay and median cost of hospitalization were highest in Winter (5.3 days, USD7459, respectively) and lowest in Summer (5.1 days, USD7181, respectively). However, age and sex differences existed (e.g. seasonal variation in inpatient mortality was only significant for patients age ≥65 years, and, compared with the Spring season, males had higher risk of inpatient mortality in Winter (OR: 1.10, 95% CI: 1.04‐1.17) and females had lower risk of inpatient mortality in Summer (OR: 0.94, 95% CI: 0.88‐1.00) and Fall (OR: 0.92, 95% CI: 0.87‐0.98). Conclusions: Among HF patients in the U.S., hospitalization outcomes were worse in Winter but better in Summer.